Investigation of the usability of industrial mining wastes in agriculture - Eker, Hasan (Frontiers in Environmental Science, 2023)
In this study, the usability of the mixtures consisting of lignite coal taken from Tekirdag region and marble and travertine wastes taken from the marble factory in Gumushane region in local bean (Kelkit) cultivation was researched. First, control samples were created using only humus soil without coal, marble, or travertine dust. Then, for each coal or coal waste, coal/coal waste—waste marble dust and coal/coal waste—travertine dust mixtures were formed. These mixtures were obtained by mixing 25%, 50%, 75%, and 100% by weight of coal and 25%, 50%, and 75% by weight of marble and travertine dust. Afterwards, local beans were planted in these mixtures and their development was followed under laboratory conditions. Additionally, temperature and humidity values were recorded at certain intervals, pH and heavy metal analysis measurements were made on the mixtures before and after bean planting, the height and leaf measurement of the beans grown and the number of beans grown in these beans were also followed, and chlorophyll analysis was performed on the bean plants grown in these mixtures. As a result, 50% Coal-3D + 50% Travertine mixture had the maximum length increase, that 25% Coal Waste (Powder)-K3 + 75% Marble mixture had the highest number of beans, and that 50% Coal Waste -AK + 50% Marble mixture had the maximum leaf formation. In these mixtures, maximum 12 beans were grown and maximum 93 leaves were formed. Also, the bean plant was grown in all mixtures. The chlorophyll contents were at least as much as the values of the beans grown only in soil. However, heavy metal values do not exceed the permissible limit values in soil.